2012
DOI: 10.1007/s10792-011-9421-4
|View full text |Cite
|
Sign up to set email alerts
|

Supratarsal injection of triamcinolone acetonide and childhood allergic keratoconjunctivitis

Abstract: To evaluate the efficacy and safety of supratarsal injection of triamcinolone acetonide in the treatment of refractory allergic keratoconjunctivitis in childhood. Thirty-five patients (70 eyes) with severe allergic keratoconjunctivitis were included in this study. Fifteen patients (42.8%) had atopic keratoconjunctivitis (AKC) and 20 (57.2%) had vernal keratoconjuncivitis (VKC). All patients underwent a bilateral supratarsal injection of 20 mg triamcinolone acetonide. Mean follow-up was 28 months (range 14-38).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…In support of such an approach, previous studies have reported a ≥50% decrease in papillae size with complete healing of a shield ulcer 12 15. Injections are repeated when the disease recurs or is recalcitrant 15. In our patient, after two injected doses, there was a 100% decrease in papillae and the corneal erosion was totally healed.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In support of such an approach, previous studies have reported a ≥50% decrease in papillae size with complete healing of a shield ulcer 12 15. Injections are repeated when the disease recurs or is recalcitrant 15. In our patient, after two injected doses, there was a 100% decrease in papillae and the corneal erosion was totally healed.…”
Section: Discussionsupporting
confidence: 78%
“…Either short-acting dexamethasone or intermediate-acting triamcinolone are equally effective with a low risk of increased intraocular pressure 12 13. In support of such an approach, previous studies have reported a ≥50% decrease in papillae size with complete healing of a shield ulcer 12 15. Injections are repeated when the disease recurs or is recalcitrant 15.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant proportion of patients are intolerant to CsA, and 16% and 5% do not respond to this treatment at month 1 and 3, respectively [1]. There are very few options in these refractory cases: supratarsal steroid injections are very potent, but may induce severe iatrogenic complications [2]; systemic steroids may be used only for a limited time; tacrolimus 0.03% skin ointment is not approved for conjunctival application, although it seems to have a very interesting effect [3]; tacrolimus 0.1% eye drops are probably also potent, but are available only in few asian countries for the moment [4]; mild cryotherapy of papillae is also an option for some [5], but we believe that there is a risk of conjunctival atrophy and scarring after repeated applications.…”
Section: Introductionmentioning
confidence: 99%
“…In a large tertiary care center study in southern 85 India, majority of the patients presented at a mean age of 12 years. 86 Additionally, most of the patients presented with a mixed variety 87 disease (72%), with adult onset of the disease (first onset at or above 88 20 years of age) occurring in only 12% of cases [68]. developments in proteomics has been outlined in Table 1.…”
mentioning
confidence: 99%
“…[33] Interferon-gamma secreted by Th1 cells has been implicated in In persistent and severe cases, supratarsal corticosteroid injection has 434 been used [86]. Aggressive limbal variants with papillae encroaching the 435 cornea can be treated by surgical excision [65].…”
mentioning
confidence: 99%